Patients' perceptions of orthodontic treatment experiences during COVID-19: a cross-sectional study - Sarah Abu Arqub; Rebecca Voldman; Ahmad Ahmida; Chia-Ling Kuo; Lucas Da Cunha Godoy; Yousef Nasrawi; Susan N. Al-Khateeb; Flavio Uribe (SpringerOpen, 2021)
Abstract Background COVID-19 has impacted the care of patients undergoing orthodontic treatment. We aimed to provide an overall view of patients' perspectives, concerns, and expectations towards their treatment throughout the clinic lockdown during the pandemic; and to assess patients' levels of mental distress and its association with their confidence in resuming care. Methods An anonymous, validated, in-person paper questionnaire was distributed to adult orthodontic patients' post-lockdown at an academic institution. The survey focused on the clinical aspects and patients' perspectives regarding orthodontic treatment during the pandemic. The Kessler Mental Distress Scale (K10) was used to evaluate their psychological status. Survey responses were descriptively summarized and confidence in resuming care was compared between normal patients and patients with mental distress using Mann-Whitney tests. Results One hundred fifty-four patients were surveyed from July to October 2020. Mean age of the participants was 29.30 (SD = 12.01) years and 62% were females. Emergencies during the closure (21%, 32/154) involved primarily irritation with protruding wires. Patients were neutral regarding tele-dentistry and preferred their current fixed appliances over clear aligners. Upon resuming care, 80.51% were extremely pleased with the restrictive protocols and with high level of confidence in resuming treatment. The average level of anxiety was low, and a modest association was found between mental distress and reduced confidence in resuming treatment. Conclusions Few numbers of minor emergencies occurred during the clinic closure. Despite the rising interest in tele-dentistry, patients were neutral on considering this option to monitor treatment and were content with fixed appliances. Patients had high confidence levels to resume their care based on the protocols established upon reopening. The association of mental distress and confidence in resuming care is suggestive and needs further investigation.